Crystal habit, characterization and pharmacological activity of various crystal forms of arteether - Renu Chadha; Sushma Gupta; Geeta Shukla (Elsevier, 2011)
The aim of this study was to investigate and characterize different crystal forms of arteether, a rapidly acting, highly potent antimalarial drug for the treatment of acute Plasmodium falciparum malaria. Six different crystal forms were prepared utilizing various polar and non-polar solvents. Scanning electron microscopy (SEM) revealed differences in the surface characteristics of the six forms from those of a commercial sample. Differential scanning calorimetry (DSC) revealed the absence of a desolvation endotherm indicating that the forms were neither hydrates nor solvates. Powder X-ray diffraction (PXRD) patterns of the forms showed much weaker major peaks than in the commercial sample indicating them to be less crystalline. Solubility and dissolution studies showed that the most amorphous form was the most soluble and possessed the highest antimalarial activity.